China's growth miracle in the context of Asian transformation - Justin Yifu Lin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Myrdal did not cover China in his Asian Drama. If he did, he would have been most likely pessimistic about China, as he was about other Asian countries in his book. However, China has achieved miraculous growth since the transition from a planned economy to a market economy at the end of 1978. This paper provides answers to the questions: Why was China trapped in poverty before 1978? How was it possible for China to achieve an extraordinary performance during its transition? Why did most other transition economies failed to achieve a similar performance? What price did China pay for its success? Can China continue its dynamic growth in the coming decades? What lessons can we draw from China's development experiences in view of Asian Drama. The paper concludes on a positive note: if a developing country adopts a pragmatic approach to developing its economy along its comparative advantages in a market economy and taps into the potential of latecomer advantages with a facilitating state, the country can grow dynamically like China.
Keywords: N15; O10; P11; 330; Chinese economy; development; rethinking economics; role of the state; transition